1997
DOI: 10.1089/aid.1997.13.1471
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Specificity of Anti-V3 Antibodies Induced in Humans by HIV Candidate Vaccines

Abstract: We analyzed the fine specificity of anti-V3 antibodies elicited in three different species (human, guinea pig, and macaque) by various HIV candidate vaccines. Following immunization with recombinant canarypox virus expressing gp160MN or with recombinant gp160MN/LAI, this antibody response was shown to be directed against the NH2-terminal region of the V3 loop. Although this response was increased by a prime-boost regimen using immunization with canarypox expressing gp160 followed by an rgp160 boost, its specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…For example, it has been shown that isolate-specific V3 responses in subtype B- and D-infected individuals are directed to residues located in the stem segments of the V3 loop (Lawoko et al, 2000; Schreiber et al, 1997) and weakly neutralizing serum antibody responses to V3 in individuals immunized with recombinant gp160 are preferentially directed to the N-terminal stem of V3 (Coeffier et al, 1997). Furthermore, in a recent study seeking to elicit 447-52D-like NAbs by utilizing fusion proteins containing the 447-52D contact epitope 305 KSIHIGPGRAFYTT 320 (Chakraborty et al, 2006), immune sera seemed to require for binding the N-terminal segment of the engrafted motif and neutralized the generally-sensitive virus MN but not the more resistant viruses BaL or JR-FL.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that isolate-specific V3 responses in subtype B- and D-infected individuals are directed to residues located in the stem segments of the V3 loop (Lawoko et al, 2000; Schreiber et al, 1997) and weakly neutralizing serum antibody responses to V3 in individuals immunized with recombinant gp160 are preferentially directed to the N-terminal stem of V3 (Coeffier et al, 1997). Furthermore, in a recent study seeking to elicit 447-52D-like NAbs by utilizing fusion proteins containing the 447-52D contact epitope 305 KSIHIGPGRAFYTT 320 (Chakraborty et al, 2006), immune sera seemed to require for binding the N-terminal segment of the engrafted motif and neutralized the generally-sensitive virus MN but not the more resistant viruses BaL or JR-FL.…”
Section: Discussionmentioning
confidence: 99%
“…In chimpanzees, candidate gp160 vaccines induce anti-V3 antibody responses that are largely restricted to the aminoterminal half of the immunizing loop [12]. When such animals are boosted with synthetic V3 peptides, however, the anti-V3 antibody repertoire broadens.…”
Section: Structural Prerequisites For Intersubtype B and D Antigenicimentioning
confidence: 99%
“…Yet one study demonstrated that a near total depletion of IgG antibody to the V3 region (measured in peptide EIA) from HIV-1 positive sera affected only minimally the capacities of the sera to neutralise primary isolates, thereby questioning the whole concept of V3 as an important epitope for neutralisation of HIV-1 in vivo [Vancott et al, 1995]. Nevertheless, there is a vast literature on V3 epitopes, which can either be broadly reactive [Javaherian et al, 1990;Blomberg et al, 1993;Cheingsong-Popov et al, 1994], or isolate specific [Boudet et al, 1996;Coeffier et al, 1997]. Isolate specific V3 epitopes are located mainly in the N-terminal half of the loop.…”
Section: Introductionmentioning
confidence: 99%